PENGARUH PERSEPSI PELAKSANAAN SCQI, KECERDASAN EMOSIONAL DAN KEINOVATIFAN TERHADAP ETIKA KERJA PEGAWAI - A.R, Aisyah (Jurnal Penelitian dan Evaluasi Pendidikan, 2012)
Penelitian ini bertujuan untuk mengetahui pengaruh persepsi terhadap pelaksanaan sitem Continous Quality Improvemen, kecerdasan emosional dan keinovatifan terhadap etika kerja pegawai di kota Palembang, dengan sampel penelitian 100 pegawai yang dilakukan secara random sampling dan data dianalisis dengan teknik analisis Structural Quation Modeling (SEM). Hasil analisis: 1) tidak terdapat pengaruh antara persepsi terhadap pelaksanaan sistem Continuous Quality Improvemen dan etika kerja pegawai, 2) terdapat pengaruh positif antara kecerdasan emosional dan etika kerja pegawai, 3) terdapat pengaruh positif antara persepsi terhadap pelaksanaan sistem  Continuous Quality Improvement dan keinovatifan 4) terdapat pengaruh positif antara  kecerdasan emosional dan keinovatifan, 5) terdapat pengaruh positif antara keinovatifan dan etika keja pegawai. Dari hasil penelitian dapat disimpulkan bahwa etika kerja pegawai dapat ditingkatkan oleh kecerdasan emosional dan persepsi terhadap pelaksanaan sistem Continuous Quality Improvement dan keinovatifan.Kata kunci: etika kerja, continous quality improvement system (CQI), kecerdasan emosional, keinovatifan______________________________________________________________THE INFLUENCE OF PERCEPTION SCQI TOWARDS EMOTIONAL QUATION AND INOVATION TOWARDS WORK ETHIC OF EMPLOYEES AT THE GOVERMENT OFFICEAbstract This study is aimed at finding out the effects of perception of the implementation of the Continuous Quality Improvement system (CQI), emotional quotient, and innovation on employees' work ethic. The study was conducted in government offices in Palembang involving 100 randomly selected employees. The data were analyzed using Structural Equation Modeling (SEM). The research findings show that: 1) there is no effect of perception of the implementation of the Continuous Quality Improvement system on employees'  work ethic, 2) there is a positive effect of employees' emotional quotient on their work ethic, 3) there is positive effect of perception of the implementation of the Continuous Quality Improvement system on innovation, 4) there is a positive effect of emotional quotient on innovation, and 5) there is a positive effect of innovation on work ethic. Based  on the research findings, it can be concluded that employees' work ethic can be enhanced by improving and developing perception of the implementation of the Continuous Quality Improvement system, emotion quotient, and innovation.Keywords: work ethic, continuous quality improvement system, emotional quotient, innovation